Rapid Molecular Diagnosis of Bacterial Infection Using Integrated Lab-on-a-disc. (2017) - Loo, J.F.C.; Leung, C.C.H.; Kwok, H.C.; Wu, S.Y.; Law, I.L.G.; Chin, M.L.; Hui, M.; Kong, S.K.; Ho, H.P.
Abstract: Bacterial infection is a disaster leading to high fatal rate in intensive caring unit. Rapid profiling of infectious bacteria is necessary for applying the correct medication. Current gold standard using plate inoculation is inaccurate, time-consuming and labour-intensive. Therefore we have developed a molecular diagnostic approach to target marker DNA of the infectious bacteria for rapid profiling. A micro-fluidic platform lab-on-a-disc (LOAD) has been adopted because using one simple spinning action can provide highly controllable centrifugation drive force for the actuation of samples and reagents anywhere within the boundary of the disc. When centrifugal force-triggered valve is applied, complex sequential flow of liquid can be controlled with various centrifugal force. This will enable parallel execution of many reactions simultaneously with minimal complexity in the design of fluidic pumping and flow control. We report an integrated LOAD for direct sample-to-answer applications - fully automated assay from patient's sample input to detection of signal output. The integrated LOAD with PDMS-made microfludic disc performs three major functions, namely DNA extraction, LAMP reaction and detection. Using microfluidics technology, target bacteria can be detected using as little as 10 μL blood sample loaded into sample loading site. The DNA release after cell lysis in heating site is bound on the silica membrane. After washing, the purified DNA elution is subjected to LAMP reaction to amplify the target genetic sequence. Loop-mediated isothermal amplification (LAMP) is an isothermal nucleic acid amplification method where reaction occurs under 65 o C. The amplified signal is reported by DNA binding fluorescent dye. Our prototype shows high yield and purity of bacterial DNA from clinical samples such as blood. We demonstrated the detection of Acinetobacter baumanii, which is one of the key pathogens resulting in hospital-acquired infections, in clinical blood sample using the LOAD platform. Fast signal detection and active temperature control within the LOAD platform has also enabled real-time LAMP targeting of specific DNA sequences as barcodes to identify infected bacterial species. We found the detection sensitivity of LAMP using DNA is 10 -15 g, while that of bacteria concentration is 10 2 cfu/ml. The system is capable of providing bacterial DNA profiling within 2 hours. In conclusion, our integrated LOAD is a simple (sample-to-answer), specific (specific genetic sequences recognition), robust (automated assay on microfluidic disc) method for rapid molecular diagnosis of bacterial infection. The short turnaround time and the technical advancement of sample-to-answer in one LOAD platform approach for rapid bacterial detection should have much potential in addressing the needs of point-of-care medical diagnosis applications. The simplicity allows the clinical healthcare workers to utilize without needing technical training.